Pelatihan Pembuatan Hand Sanitizer pada Pemuda Karang Taruna Desa Mojokambang Kabupaten Jombang - Iin Baroroh Ma'arif; Ospa Pea Yuanita Meishanti; Siti Aminatuz Zuhria; Anisa Anisa (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The activity is in the form of training in making hand sanitizers for youth organizations in Mojokambang village, Jombang district. This activity aims to increase public understanding about making hand sanitizers independently which is easy and inexpensive. This activity was followed by 25 participants and held for 3 days starting 26-28 October 2020 at balaidesa Mojokambang. The methods used in this activity are socialization, discussion and training / practice. The results of this activity are expected to be able to assist the community in increasing awareness in protecting themselves and the environment against the spread of the Covid 19 virus by making hand sanitizers independently that are easy and inexpensive. Keywords: Training, Hand Sanitizer, YouthOrganization.